The comparison of European Union banking sector with Turkish banking sector - Erkoç, Gökşen (My University, 2008)
Avrupa Birliği’nin kuruluşundan sonra, birlik yıllar itibariyle hem derinleşmekte hem de genişlemektedir. Bugün yirmi yedi üye ülkeden oluşan Avrupa Birliği, sınırları Maastricht Anlaşması ile belirlenmiş tek para ile ortak pazarı tamamlamakta büyük bir adım atmış ve parasal birliğe geçmiştir. Birliğin kurulduğu yıllarda, tek para birimine ihtiyaç duyulmamakta idi. O zamanlar, Bretton Woods sistemi ile bütün dünya ortak para alanı haline gelmişti. Bretton Woods sisteminin yıkılmasından sonra, Birlik parasal birliği gerçekleştirmek için tek para birimine ihtiyaç duydu. Ekonomik ve parasal birliğin, tek para birimi ile eş anlı gerçekleştirilebilmesi için finansal piyasalarda bütünleşmenin sağlanması gerekliydi. Ev sahibi ülkeyi tanımaya dayanan birinci bankacılık direktifi, bankacılık sektörünün bütünleşmesi için faydalı olamamıştır. Menşei ülkeyi tanımaya dayanan ve tek pasaportu tanıtan ikinci bankacılık direktifi, bankacılık sektörünün bütünleşmesi için en büyük adımdır. Günümüzde Avrupa Birliği bankacılık sektörü eski üyeler arasında bütünleşmiştir. Yeni üye devletlerin, Avrupa Birliği eski üyelerinin yerini yakalabilmesi için önlerinde çok uzun yol vardır. Türkiye’nin Avrupa Birliği’ne girme beklentisi, politik ve ekonomik reformlarda yapılan ilerlemelere bağlıdır. Finansal sektördeki birçok konu bankacılık sektörü ile ilgidir. Çünkü Türk finansal sisteminin aktif toplamının yüzde doksanını bankacılık sektörü oluşturmaktadır. Geçmişte, bazen Türkiye’nin ekonomik durumu bankacılık krizlerine, bazen de bankacılık krizleri Türkiye’de ekonomik krizlere neden olmuştur. Bununla birlikte, 2000-2001 ekonomik krizinden sonra, Türk bankacılık sektörü, rehabilitasyon programına tabi oldu. Sektörün yapısal problemleri çözülmeye başlandı. Türk bankacılık piyasası büyük bir büyüme potansiyeline sahiptir. AB’nin yeni üye devletleri üzerinde ve eski üyelerin arasında, teknolojik altyapısı, kalifiye iş gücü, karlılık, verimlilik ve büyüme potansiyeli açısından rekabet avantajı vardır.

After the foundation of the European Union, the Union has been both deepening and enlargening over the years. The European Union which consists of twenty seven member states today has taken a big step for the fulfillment of the common market and has passed through the monetary union with single currency whose border was drawn by the Maastricht Treaty. There was no need to have a single currency when the Union was established. With the Bretton Woods system, the whole world became a common currency area at that time. After the failure of the Bretton Woods system, the Union needed to have a single currency to realize the monetary union. The integration had to be maintained in the financial market to realize the economic and monetary union with the common currency synchronously. The first banking directive which depended on the host country recognition could not be useful for the integration of the banking sector. The second banking directive which depended on home country rule and which introduced the single passport was the biggest step for the integration of the banking sector. Today, EU banking sector has been integrated among the old member states, there is a long way in front of the new accession countries to catch the place of the old member states. Turkey’s prospects of accession to the European Union are highly dependent on the progress made with political and economic reforms. Most of the issues are concentrated in the banking sector in financial sector, because banks account for more than ninety percent of the total assets of the Turkish financial system. In the past, sometimes, the economic situation of Turkey caused banking crises, sometimes; the banking crises caused economic crises in Turkey. However after the 2000-2001 economic crises, Turkish banking system has to be dependent on a rehabilitation programme. The structural problems of the sector has been started to be solved. Turkish banking market has a big potential to grow up. It has competitive advantage over the new accession countries and among the EU old member states in terms of its technological infrastructure, its qualified staffs, its profitability, its effectiveness and the growing potential.
Keywords: Bankalar ve Bankacılık; Uluslararası Bankacılık